2023
DOI: 10.2147/jir.s399284
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Contributes to Inflammatory and Cellular Damage in Systemic Lupus Erythematosus: Cellular Markers and Molecular Mechanism

Abstract: Systemic lupus erythematosus (SLE) is a multifactorial autoimmune disease with complex pathogenesis, the treatment of which relies exclusively on the use of immunosuppressants. Increased oxidative stress is involved in causing inflammatory and cellular defects in the pathogenesis of SLE. Various inflammatory and cellular markers including oxidative modifications of proteins, lipids, and DNA contribute to immune system dysregulation and trigger an aggressive autoimmune attack through molecular mechanisms like e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 95 publications
1
7
0
Order By: Relevance
“…The comparison of expression differences between groups were later performed based on the expression of immune and oxidative stress-related genes, respectively. With the progression of SLE, immune and oxidative stress gradually show high levels of activity, which is consistent with the current ndings [8,12] . The main mechanism of SEP is infection-induced immunosuppression [49] , and oxidative stress makes enhances endothelial dysfunction promoting disease progression [50] .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The comparison of expression differences between groups were later performed based on the expression of immune and oxidative stress-related genes, respectively. With the progression of SLE, immune and oxidative stress gradually show high levels of activity, which is consistent with the current ndings [8,12] . The main mechanism of SEP is infection-induced immunosuppression [49] , and oxidative stress makes enhances endothelial dysfunction promoting disease progression [50] .…”
Section: Discussionsupporting
confidence: 92%
“…Oxidative stress has also been linked to the pathogenesis of SLE by suppressing FOXP3 expression, Treg cell differentiation, and lipid peroxidation metabolites [11,12] . Further r studies have revealed that the tolllike receptor pathway, the HIF-1 pathway, and the mTOR pathway play essential roles in immunological and metabolic regulation during the host response to infection [13,14] .…”
Section: Introductionmentioning
confidence: 99%
“…Various markers induce oxidative modifications of proteins, lipids, and DNA, leading to immune system dysfunction and a fierce autoimmune assault. Some of the indicators are improved NETosis, stimulation of the mTOR pathway, and disrupted T‐cell differentiation caused by molecular mechanisms 18,19 …”
Section: Discussionmentioning
confidence: 99%
“…Some of the indicators are improved NETosis, stimulation of the mTOR pathway, and disrupted T-cell differentiation caused by molecular mechanisms. 18,19 According to certain scientists, bilirubin is a powerful antioxidant that can potentially offer cellular defense against detrimental stimuli. 20 Several studies have indicated a strong correlation between serum bilirubin levels and SLE.…”
Section: Discussionmentioning
confidence: 99%
“…Arterial hypertension is associated with OS, and its presence in SLE implies a dysregulated ratio of Th1/Th2 cytokines, increased production of IL-17, and insulin resistance. By augmenting the susceptibility of the tiny renal inlet arteries to angiotensin II and the expression of sodium chloride co-transporters, OS may enhance the reabsorption of water and sodium in the renal tubules, precipitating the development of hypertension [77,78]. Nuclear factor E2-related factor 2 (Nrf2) is a vital regulator of the antioxidant response in LN.…”
Section: Lupus Nephritismentioning
confidence: 99%